71.4k views
1 vote
I need help and i dont know how to do the work of it​

I need help and i dont know how to do the work of it​-example-1
User Aniket Rao
by
4.9k points

1 Answer

4 votes

Answer:

Explanation:


xy=5, y=-2x-8
Using substitution,


x(-2x-8)=-5\\-2x^(2)-8x=-5\\2x^(2)+8x-5=0\\x=\frac{-8 \pm \sqrt{8^(2)-4(2)(-5)}}{4}\\x=(-8 \pm √(104))/(4)\\x=-2 \pm √(13/2)

So, if
x=-2+√(13/2), y=
-2(-2+√(13/2))-8=4-√(26)

And if
x=-2-√(13/2),
y=-2(-2-√(13/2))=√(26)-4

User Umutesen
by
5.1k points